DAMPAK TRUST ISSUE DALAM KONTEN INSTAGRAM TERHADAP KOMUNIKASI ANTAR PERSONAL : (ANALISA KONTEN INSTAGRAM @LOVAYANK) - Arie Sukmawati; Hery B Cahyono (MEDIAKOM, 2023)
Trust Issue has become a topic that is often discussed by many people. In the context of personal relationships, this trust issue often occurs due to suspicion, betrayal or painful past experiences. This issue is very common and also has a significant impact on a person's life, both personally and socially, no wonder many relationships are 'destroyed' because of this trust issue. Things that usually happen in the scope of trust issues include marriage, romantic relationships and friendships. The problem of trust in this relationship has finally been raised by many Instagram social media activists to become a quote content in the form of text or video. Not a few netizens responded to the uploaded content, some justified the content, telling an experience, fear reaction, overthinking. Therefore, researchers are interested in exploring further by conducting a content analysis of Krippendorff to find out the description of the trust issue itself and the impact caused by the trust problem. The method used by researchers uses a qualitative descriptive method by including 5 samples from the @lovayank account and Netizen comments as the object of this research. The results of the study show many negative reactions to one of the video content quotes @lovayank which is an indicator of the description and impact of the trust issue.